2020
DOI: 10.1111/cea.13740
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal Phleum pratense allergoid immunotherapy. Double‐blind, randomized, placebo‐controlled trial

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Only two double-blinded placebo-controlled trials with conflicting results have been conducted regarding IDIT ( 30 31 ). The first of these studies reported that daily combined symptom-medication scores (CSMSs) in the active group, a parameter strongly recommended as a primary end point in evaluating the treatment efficacy of AIT, did not differ from daily CSMSs in the placebo group ( 30 ) ( Fig.…”
Section: Therapeutic Efficacy Of Aits With Alternative Routes Of Admi...mentioning
confidence: 99%
See 2 more Smart Citations
“…Only two double-blinded placebo-controlled trials with conflicting results have been conducted regarding IDIT ( 30 31 ). The first of these studies reported that daily combined symptom-medication scores (CSMSs) in the active group, a parameter strongly recommended as a primary end point in evaluating the treatment efficacy of AIT, did not differ from daily CSMSs in the placebo group ( 30 ) ( Fig.…”
Section: Therapeutic Efficacy Of Aits With Alternative Routes Of Admi...mentioning
confidence: 99%
“…The small quantity of allergen (7 ng of the major allergen Phl p 5) in a small volume (20 μL) may further induce Th2 rather than Th1 or Treg immunity, resulting in low therapeutic efficacy, although intradermal injection of allergens may promote drainage of allergens into LNs. Conversely, the second study found that IDIT reduced CSMSs and serum allergen-specific IgE levels, while increasing allergen tolerance in the conjunctival provocation test ( 31 ). In both studies, grass pollen allergens ( Phleum pratense ) were injected weekly in six total administrations.…”
Section: Therapeutic Efficacy Of Aits With Alternative Routes Of Admi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Allergoids are modified allergen extracts whose allergenicity has been reduced with preserved immunogenic activity [ 36 ]. Allergoids are commonly administered subcutaneously; however, Martinez et al [ 37 ] conducted the first randomized controlled trial (RCT) in IDIT using P. pratense allergoid with a satisfactory result. Subjects were randomized to receive six intradermal weekly injections of placebo, low-dose allergoid, or high-dose allergoid.…”
Section: Modified Formulations Of Intradermal Immunotherapymentioning
confidence: 99%
“…A new tool for assessing quality of life called RAPP was developed and shows promise for combining quality of life assessment for asthma and rhinitis 21 . Intervention trials included a new form of nasal steroid and a new form of grass pollen immunotherapy 22‐24 …”
Section: Rhinitismentioning
confidence: 99%